1978
DOI: 10.1126/science.345441
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin: A Potentially Valuable Agent for Preserving Myocardial Tissue in Acute Myocardial Ischemia

Abstract: Prostacyclin, a potent, naturally occurring prostaglandin exerts a variety of cardiovascular and cellular actions of potential value in acute myocardial ischemia. These properties include the reduction of systemic blood pressure without changing heart rate, the lowering of coronary vascular and total peripheral resistance, the inhibition of platelet aggregation and the concomitant formation of thromboxane B2, and the reduction of the release of lysosomal enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(57 citation statements)
references
References 28 publications
4
52
1
Order By: Relevance
“…These data, along with the observation that significant numbers of platelet emboli are not present in small pulmonary vessels as demonstrated by electron microscopy, suggest that PGI2 has the ability to reverse the aggregation process in vivo in the pulmonary vascular bed. The present results are in agreement with in vitro studies with the aggregometer in whch PGI2 was a potent inhibitor of platelet aggregation Gryglewski et al, 1976;Lefer et aL, 1978). It has been reported recently that isolated perfused lungs of rats and guinea pigs and the lungs of anesthetized cats spontaneously release a "PGI2-like" substance (Gryglewski et aL, 1978).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data, along with the observation that significant numbers of platelet emboli are not present in small pulmonary vessels as demonstrated by electron microscopy, suggest that PGI2 has the ability to reverse the aggregation process in vivo in the pulmonary vascular bed. The present results are in agreement with in vitro studies with the aggregometer in whch PGI2 was a potent inhibitor of platelet aggregation Gryglewski et al, 1976;Lefer et aL, 1978). It has been reported recently that isolated perfused lungs of rats and guinea pigs and the lungs of anesthetized cats spontaneously release a "PGI2-like" substance (Gryglewski et aL, 1978).…”
Section: Discussionsupporting
confidence: 81%
“…PGI 2 relaxes strips of mesenteric and celiac arteries but not strips from aorta and vena cava . Prostacyclin decreases systemic arterial pressure in all species in which it has been studied, and a PGI 2 analog has been shown to have marked vasodilator activity in the feline pulmonary lobar and mesenteric vascular beds Paustian et al, 1977;Armstrong et al, 1978;Fitzpatrick et al, 1978;Lefer et al, 1978). Although PGI 2 is formed in blood vessels, "PGl2-like" substances are released from the lung, and the metabolite, 6-keto-PGFi a , is released from the lung after immunological challenge, the direct effects of PGI 2 on the pulmonary vascular bed are uncertain (Dawson et al, 1976;Gryglewski et aL, 1976;Gryglewski et al, 1978).…”
mentioning
confidence: 99%
“…Prostacyclin has been shown to have a cardioprotective effect during acute myocardial ischaemia and reperfusion (Lefer et al, 1978;Ogletree et al, 1979;Araki et al, 1980;Jugdutt et al, 1981;Schror et al, 1981;Melin et al, 1983;Berti et al, 1990), although the exact mechanism for this cardioprotective effect is still unclear. The present study suggests that, like prostacyclin, beraprost may have cardioprotective effects with respect to both action potential and contractile force in guinea-pig ventricular muscles during hypoxia-reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to inotropic effects of prostacyclin, contradictory results have been reported. Lefer et al (1978) showed that prostacyclin does not produce any direct inotropic effect on electrically driven papillary muscles of the cat but Fassina et al (1983) described positive inotropic effects of prostacyclin, on guinea-pig isolated atria. This was also confirmed by the fact that the shortening of APD induced by 50pmoll1' pinacidil was not antagonized by beraprost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation